Implementation of a multiple beamformer for coarse localization of passive UHF RFID tags - Flores, Roy Repalda
This study describes a testbed for coarse localization of passive UHF RFID tags by using a multiple beamformer network. The coarse localization is achieved by specifying the sector location of a tag and estimating its distance from the antennas. The multiple beamformer is composed of a four-element linear array of circularly polarized microstrip patch antennas and a 4x4 Butler matrix. The design, simulation, implementation and characterization of these components are discussed. Localization experiments were done to characterize the system. For multiple tag localization, the read percentage is 90.54%. Increasing the number of tags in the area from 4 to 13 degraded the read percentage by almost 20%.The overall accuracy of the sector estimates reaches 76.51%. Increasing the number of tags in the area increases both the false positives in the inner beams and the false negatives in the outer beams. The average error distance is 0.19 meters; hence, the coarse localization is accurate within 0.2 meters.